Implementing a successful patient navigation program for follow-up colonoscopy: Lessons from the PRECISE study - Jamie H. Thompson; Jennifer L. Schneider; Jennifer S. Rivelli; Priyanka Gautom; Jeffery Gibbs; Neha Yadav; Ricardo Jimenez; Gloria D. Coronado (PLoS ONE, 2026)
Background Colorectal cancer (CRC) screening using annual fecal immunochemical tests (FIT) is an effective strategy to reduce CRC incidence and mortality. However, nearly 50% of patients with abnormal FIT results fail to complete the necessary follow-up colonoscopy. Patient navigation (PN) can provide crucial support for colonoscopy completion. Despite PN’s effectiveness, there is limited knowledge about its optimal implementation in community health settings. This manuscript presents lessons learned from a PN intervention, including successes, challenges, and recommendations, which are essential for improving future PN programs in community health centers. Methods The PRECISE study is a patient-randomized trial of PN vs usual care for follow-up colonoscopy at a Federally Qualified Health Center in Washington state. The comprehensive implementation support for the patient navigation intervention included trainings, technical assistance, and quality assurance session to equip navigators with the skills needed to effectively guide patients to colonoscopy completion. Study staff tracked implementation support adaptations and lessons learned using data sources including PN training program reflections and patient navigator debrief interviews . We examined successes, challenges, and recommendations in five main categories: 1) patient navigation delivery, 2) implementation support and quality assurance, 3) staffing, 4) partnerships and resources, and 5) data tracking. Results Navigators found the training sufficient to successfully implement the program, but pointed to challenges related to workloads, documentation, and partnerships with gastroenterology practices. Key lessons learned included streamlining patient navigation topics to enhance outreach, maintaining effective implementation support and quality assurance elements, ensuring adequate staffing, fostering partnerships with GI practices, and implementing unified data tracking systems. Conclusion Our findings can guide future efforts to implement and sustain patient navigation programs for follow-up colonoscopy after abnormal FIT testing in community-based settings.